Development of a burger supplemented partially with king worm meal (Zophobas morio) in Bogotá and surrounding municipalities - Muñoz-Castillo, Juan Sebastian
Entomophagy has emerged as an interesting nutritional and functional alternative to meet the demands of the population and address climate change mitigation and adaptation. The project involves a feasibility analysis for the development of hybrid products, such as a burger in this case, where the traditional meat matrix is replaced with mealworm flour (Zophobas morio) in varying concentrations. The project is currently in the experimental phase, with nutritional content data already collected, emphasizing protein and lipid content, including unsaturated fatty acids. Currently, the project is in the data analysis phase, alongside surveys with panelists using hedonic affective tests. To date, 75 citizens within the age range of twelve to eighty years have been surveyed. From the overall feedback gathered through discussions with the panelists, a distinct preference for hybrid formulations has been identified, acknowledging new attributes such as crispiness and intense flavor in the product. The purpose of this research is to highlight the quality and potential of this alternative protein source. Thus, the goal is to gradually incorporate these products into diets by enriching traditional food industries with powdered products. This approach appears to be the best option for gaining acceptance from the population, considering the aversion to insects and neophobia towards novel products held by certain individuals.